2018
DOI: 10.1139/cjps-2017-0258
|View full text |Cite
|
Sign up to set email alerts
|

Response of Bosc and Cold Snap™ pears to thinning with NAA, 6-BA, ACC, and s-ABA

Abstract: Adjusting the crop load of European pears (Pyrus communis L.) by hand thinning is currently required to ensure marketable size of most cultivars grown in Ontario. The benefits of thinning pears chemically and its effect on fruit quality and fresh-market returns were investigated in a 3-yr study where a series of foliar chemical thinning sprays were applied during the 10-mm fruitlet stage to Bosc and Cold Snap™ pear trees growing in commercial orchards in the Niagara Peninsula, Ontario. Treatments included an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The thinning activity of metamitron on apple was associated with reduced Fv/Fm values (McArtney et al, 2012). Indirect photosynthetic inhibition by ABA was also associated with fruitlet abscission of apple (McArtney et al, 2014) and pear (Arrington et al, 2017;Einhorn and Arrington, 2018); however, the consistent thinning of pear by ABA (Arrington et al, 2017;Cline et al, 2018;Greene, 2012) was not similarly demonstrated for apple (McArtney et al, 2014;Greene, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…The thinning activity of metamitron on apple was associated with reduced Fv/Fm values (McArtney et al, 2012). Indirect photosynthetic inhibition by ABA was also associated with fruitlet abscission of apple (McArtney et al, 2014) and pear (Arrington et al, 2017;Einhorn and Arrington, 2018); however, the consistent thinning of pear by ABA (Arrington et al, 2017;Cline et al, 2018;Greene, 2012) was not similarly demonstrated for apple (McArtney et al, 2014;Greene, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…In cv. 'Forelle', Theron et al [64] found differing responses to ABA application between regions and years, and Cline et al [49] reported inconsistent results over the three years of their study on cvs. 'Cold Snap TM ' and 'Bosc', but did find that 300 mg/L had a greater thinning effect than 150 mg/L.…”
Section: Abscisic Acid (Aba)mentioning
confidence: 97%
“…Fruit size distribution was shifted in this study by both dose rates, but the effect was greater at the higher application rate of 100 mg/L with more fruit in the larger size categories and reduced numbers in the small size categories. Cline et al [49] reported that in Ontario Canada, 150 mg/L BA at the 10 mm fruitlet stage was more consistent as a thinner of cvs. 'Bosc' and 'Cold Snap TM ' than 100 mg/L, but as crop load was not heavy, crop value was reduced compared with untreated trees due to a reduction in yield.…”
Section: -Benzyladeninementioning
confidence: 99%
See 2 more Smart Citations